Impact of English Language Teaching and Learning through Language Laboratory in Engineering in Nepal - Shrestha, Rup Narayan; Pahari, Bharat; Awasti, Jai Raj (Journal of the Institute of Engineering, 2014)
The present article discusses the importance of language, in general, and English, in particular, in the context of engineering education in Nepal. It mainly discusses the importance and application of language laboratory for the enhancement of skills and proficiency of English language in the learners of Bachelor's level in engineering in Nepal. The main objective of the present article is to highlight the importance of teaching and learning of English language in the B.E. level in engineering by using language laboratory. In course of the present study, literature available in different accessible sources was reviewed for collecting necessary data and designing theoretical framework for the same. From the study, it has been found that language laboratory is tremendously helpful in creating favourable atmoshphere for language learning and helping the learners to acquire necessary language skills useful to them in sharpening their study at present and streamlining their research and innovative activities in their further studies in the future. English language is now the language of worldwide communication, and therefore, it is very essential for the students of engineering to be proficient in communication through English not only for grabbing job opportunities open at present but also to furthering their future research and innovative endeavors and publishing their reports and research articles based on them. Language Laboratory is highly instrumental for attaining ample proficiency in English language, the means of global communication. DOI: http://dx.doi.org/10.3126/jie.v10i1.10882 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014, pp. 94–103